Political theology as theodicy: The holy spirit's performance in the economy of redemption - Grassi, Martín (2021)
Although Political Theology examined mainly the political dimension of the relationship between God-Father and God-Son, it is paramount to consider the political performance of the Holy Spirit in the Economy of Redemption. The Holy Spirit has been characterized as the binding cause and the principle of relationality both referring to God´s inner life and to God´s relationship with His creatures. As the personalization of relationality, the Holy Spirit performs a unique task: To bring together what is apart by means of organisation. This power of the Spirit to turn a plurality into a unity is manifested in the Latin translation of oikonomía as disposition, that is, giving a special order to the multiple elements within a certain totality. Within this activity of the Spirit, Theodicy can be regarded as the way to depict God´s arrangement of the world and of history, bringing everything together towards the eschatological Kingdom of God. The paper aims at showing this fundamental activity of the Holy Spirit in Christian Theology, and intends to pose the question on how to think on a theology beyond theodicy, that is, how to think on a Trinitarian God beyond the categories of sovereignty and totalization.